Welding material and method for preparing aluminum-steel gradient structure

Through laser melting+CMT composite preparation method, the aluminum-steel gradient structure is prepared to solve the problem of not matching the thermal properties and brittleness of the aluminum-steel heterogeneous structure welding. Improvement of joint performance.

CN119328361AActive Publication Date: 2025-01-21XIAN UNIV OF TECH

Patent Information

Application Number
CN202411592405.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-21
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

During welding, aluminum-steel heterogeneous structures lead to cracking and poor performance due to mismatch of thermal physical properties and the formation of brittle phases.

Method used

Use laser melting+CMT composite preparation method, use laser melting alloy powder and CMT welding wire for aluminum-based welding wires to prepare the Al-Zn-CU-SI alloy layer on the steel base through laser melting, and perform CMT on it on it Welding for pile, and finally the aluminum layer is welded with an arc to form an aluminum-steel gradient structure.

Benefits of technology

It effectively blocks the generation of brittle phases between Al and Fe elements, improves the joint performance of aluminum-steel gradient structures, solves the problems of cracking and poor performance, and has broad industrial promotion value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119328361A_ABST
    Figure CN119328361A_ABST
Patent Text Reader

Abstract

The invention discloses a welding material for preparing an aluminum-steel gradient structure. The welding material comprises alloy powder for laser cladding and an aluminum-based welding wire for CMT welding. The alloy powder for laser cladding comprises the following components in percentage by mass: 20.0%-30.0% of Zn powder, 20.0%-30.0% of Cu powder, 5.0%-10.0% of Si powder, 5.0%-10.0% of Sn powder and the balance of Al, the aluminum-based welding wire for CMT welding comprises powder and a welding skin, and the powder comprises, by mass, 20.0%-30.0% of Zn powder, 20.0%-30.0% of Ag powder, 10.0%-20.0% of Cu powder, 5.0%-10.0% of Si powder, 5.0%-9.0% of Mg powder and the balance Al powder. The structure solves the problems of cracking and poor performance caused by mismatching of thermal physical properties and brittle phases of an aluminum-steel dissimilar structure. The invention further provides a laser and CMT composite preparation method of the aluminum-steel gradient structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of metal materials, and in particular relates to a welding material for preparing an aluminum-steel gradient structure, and also relates to a laser+CMT composite preparation method of the aluminum-steel gradient structure. Background Art

[0002] Aluminum is a silvery white light metal with a melting point of 660°C and a density of 2.7 g / cm 3 . Aluminum and its alloys have the characteristics of light weight, high specific strength, good thermal conductivity, electrical conductivity and corrosion resistance, and can maintain good mechanical properties under low temperature conditions; while steel has become one of the most used materials in the world due to its low price and reliable performance. It has always been in a dominant position in the manufacturing industry and has excellent cold and hot processing performance, plasticity and toughness, and corrosion resistance. Aluminum / steel dissimilar metal composite structures can give full play to the inherent advantages of both materials, with the advantages of light weight, high strength and good corrosion resistance, and are increasingly widely used in the fields of automobile manufacturing, aerospace, etc.

[0003] The weldability of dissimilar metal materials depends on the metallurgical characteristics and thermophysical properties of the two. When the physical and chemical properties of the two metals to be welded are very different and the mutual solubility is very low, a large amount of brittle and hard intermetallic compounds are easily produced, which seriously reduces the mechanical properties of the dissimilar metal welded joints. The same problems also exist in aluminum / steel dissimilar metal welding. Due to the low solid solubility between aluminum and steel, the large difference in thermophysical and mechanical properties, and the easy formation of hard and brittle intermetallic compounds, aluminum / steel welding connection becomes difficult. Summary of the invention

[0004] The purpose of the present invention is to provide a welding material for preparing an aluminum-steel gradient structure, which solves the problems of cracking and poor performance caused by the mismatch of thermal physical properties of aluminum-steel dissimilar structures and the brittle phase.

[0005] Another object of the present invention is to provide a laser + CMT composite preparation method for an aluminum-steel gradient structure.

[0006] The first technical solution adopted by the present invention is that the welding material for preparing the aluminum-steel gradient structure includes alloy powder for laser cladding and aluminum-based welding wire for CMT welding; The alloy powder for laser cladding includes the following components by mass percentage: Zn powder 20.0-30.0%, Cu powder 20.0-30.0%, Si powder 5.0-10.0%, Sn powder 5.0-10.0%, and the balance is Al; The aluminum-based welding wire for CMT welding comprises flux powder and welding skin, wherein the flux powder comprises the following components by mass percentage: Zn powder 20.0-30.0%, Ag powder 20.0-30.0%, Cu powder 10.0-20.0%, Si powder 5.0-10.0%, Mg powder 5.0-9.0%, and the rest is Al powder.

[0007] The present invention is also characterized in that: The purity of each raw material powder in the laser cladding alloy powder is ≥99.9%.

[0008] The particle size of each raw material powder in the aluminum-based welding wire for CMT welding is 100~200 mesh.

[0009] The weld skin of aluminum-based welding wire for CMT welding is pure aluminum strip with a thickness of 0.4mm and a width of 7mm.

[0010] The powder filling rate of aluminum-based welding wire for CMT welding is controlled at 25wt%~30wt%.

[0011] The preparation method of alloy powder for laser cladding includes the following specific steps: Step 1: Weigh 20.0-30.0% Zn powder, 20.0-30.0% Cu powder, 5.0-10.0% Si powder, 5.0-10.0% Sn powder, and the balance Al, respectively, and the sum of the mass percentages of the above components is 100%; Step 2: Mix the raw material powders in step 1, melt them in vacuum, and prepare powder by gas atomization method; In step 2, vacuum melting equipment is used, N2 is used as atomizing gas, the atomizing pressure is 6MPa, and the superheat of the melt is maintained between 100 and 150°C during the atomization process; Step 3: Screening the atomized raw material powder for particle size; In step 3, the particle size range of the raw material powder after sieving is 25 μm~53 μm, that is, 270~500 mesh.

[0012] The fluidity requirement of the raw material powder after screening is 25s / 100g ~40s / 100g.

[0013] Step 4: Vacuum pack the prepared powder for later use.

[0014] The preparation method of aluminum-based welding wire for CMT welding, the specific steps are as follows: Step 1: Weigh 20.0-30.0% Zn powder, 20.0-30.0% Ag powder, 10.0-20.0% Cu powder, 5.0-10.0% Si powder, 5.0-9.0% Mg powder, and the rest Al powder, respectively, by mass percentage, and the sum of the mass percentages of the above components is 100%; Step 2: The powder weighed in step 1 is placed in a vacuum heating furnace and heated at a temperature of 100-160°C for 1-2 hours to remove the crystal water in the powder; the dried powder is placed in a powder mixer for sufficient mixing for 1-2 hours; Step 3: Use alcohol to remove grease from the surface of the pure aluminum strip, and wrap the powder prepared in step 2 in the pure aluminum strip through a flux-cored wire drawing device. The aperture of the first drawing die is 2.6 mm; the powder filling rate is controlled at 25wt%~30wt%; Step 4: After the first drawing process is completed, the die aperture is reduced successively, and finally a flux-cored welding wire with a diameter of 1.2 mm is obtained; Step 5: After the flux-cored welding wire is drawn, it is wound on the welding wire reel by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for standby use.

[0015] The second technical solution adopted by the present invention is a laser + CMT composite preparation method of an aluminum-steel gradient structure, which uses the prepared laser cladding powder and aluminum-based welding wire for CMT welding to prepare an aluminum-steel gradient structure, and the specific steps are as follows: (1) First, the above alloy powder for laser cladding is used to prepare a laser cladding layer on a steel substrate (Q345), the laser power is 1 kW to 3 kW, and the thickness of the cladding layer is 1.0 mm to 1.5 mm; (2) Next, the above-mentioned aluminum-based welding wire for CMT welding is used to perform cladding welding on the above-mentioned laser cladding layer. When the first layer is cladding welded, the welding current is 150A~180A, and the thickness of the cladding layer is 2mm~3mm; when the second layer is cladding welded, the welding current is 180A~200A, and the thickness of the cladding layer is 3mm~4mm; during CMT cladding welding, the interlayer temperature is controlled at 50℃~100℃; (3) Finally, ER1100 pure aluminum welding wire is used to perform arc cladding on the second CMT cladding layer to prepare an aluminum layer. The welding current is 150A~200A, the thickness of the cladding layer is 10mm~15mm, and the interlayer temperature is controlled at 50℃~100℃ during cladding.

[0016] The beneficial effects of the present invention are: (1) The present invention adopts the laser cladding + CMT arc composite process to prepare the aluminum-steel gradient structure, which fully utilizes the advantages of high laser cladding precision and high CMT arc cladding efficiency, thereby obtaining a high-quality aluminum-steel gradient structure and having broad industrial promotion value. It solves the problems of cracking and poor performance caused by the mismatch of thermal physical properties of aluminum-steel dissimilar structures and brittle phases.

[0017] (2) The inventive method first prepares a laser cladding layer on a steel substrate. The cladding layer is mainly composed of an Al-Zn-Cu-Si alloy system. The added Zn, Cu, and Si have a high solid solubility in aluminum, which can fully guarantee the quality of the laser cladding layer. In addition, these elements have a low melting point. When the laser cladding layer is prepared on steel, the dilution rate is low, and the effect of fusion brazing is achieved.

[0018] (3) The aluminum-based welding wire for CMT arc cladding of the present invention is prepared by cladding on a laser cladding process. The welding wire is mainly composed of Al elements, and alloy elements such as Zn, Ag, and Cu are added. The welding wire has a low melting point, and the cladding layer and the laser cladding layer have good metallurgical bonding.

[0019] (4) The laser + CMT composite preparation method of the aluminum-steel gradient structure of the present invention can effectively block the formation of brittle phases between Al and Fe elements, thereby ensuring the joint performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 Schematic diagram of preparing an aluminum-steel gradient structure by the laser + CMT composite preparation method of the aluminum-steel gradient structure used in the present invention; Figure 2 The microstructure of the laser cladding layer in the aluminum-steel gradient structure prepared in Example 2; Figure 3 The microstructure of the CMT cladding layer in the aluminum-steel gradient structure prepared in Example 2; Figure 4 The tensile fracture morphology of the aluminum-steel gradient structure prepared in Example 2 was observed by scanning electron microscopy. DETAILED DESCRIPTION

[0021] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0022] The present invention provides welding materials for preparing aluminum-steel gradient structures, including alloy powder for laser cladding and aluminum-based welding wire for CMT welding; The alloy powder for laser cladding includes the following components by mass percentage: Zn powder 20.0-30.0%, Cu powder 20.0-30.0%, Si powder 5.0-10.0%, Sn powder 5.0-10.0%, and the balance is Al; The aluminum-based welding wire for CMT welding comprises flux powder and welding skin, wherein the flux powder comprises the following components by mass percentage: Zn powder 20.0-30.0%, Ag powder 20.0-30.0%, Cu powder 10.0-20.0%, Si powder 5.0-10.0%, Mg powder 5.0-9.0%, and the rest is Al powder.

[0023] The roles and functions of the main components in laser cladding alloy powder and CMT welding wire are as follows: (1) A large amount of Al is added to both the laser cladding alloy powder and the CMT welding wire: The laser cladding layer is prepared on a steel substrate, and the addition of Al can ensure good metallurgical bonding between the laser cladding layer and the arc cladding layer. The CMT cladding layer is connected to the laser cladding layer on one side and to the aluminum layer on the other side. Therefore, the CMT cladding layer contains a large amount of Al, which can ensure metallurgical bonding with both the laser cladding layer and the aluminum layer.

[0024] (2) A large amount of Zn is added to both the laser cladding alloy powder and the CMT welding wire: From the Al-Zn binary phase diagram, it can be seen that Zn is the element with the highest solid solubility in Al (the maximum solid solubility is 83.1wt.%), and Zn has a low melting point. Therefore, adding Zn to the laser cladding layer on steel can not only improve the metallurgical quality of the cladding layer itself, but also reduce the melting point of the cladding layer, so that its dilution rate is low when cladding on the steel substrate, thereby inhibiting the Fe element in the steel from entering the laser cladding layer. The role of Zn in CMT welding wire is similar to that in laser cladding layer. It can ensure that the welding wire has good metallurgical bonding performance (ensuring that the CMT cladding layer is well bonded with the laser cladding layer and that the CMT cladding layer is well bonded with the aluminum layer above), and can also reduce the melting point of the welding wire, thereby reducing the mutual diffusion between elements.

[0025] (3) A large amount of Cu element is added to both laser cladding alloy powder and CMT welding wire: From the Al-Cu binary phase diagram, it can be seen that the solid solubility of Cu in Al is also high. The laser cladding layer is deposited on the steel substrate. From the Cu-Fe binary phase diagram, it can be seen that no brittle phase will be generated between the two. Therefore, adding Cu to the laser cladding layer can ensure the bonding performance between the cladding layer and the steel substrate. Adding Cu to the CMT welding wire can dissolve Cu in Al and improve the strength of the CMT cladding layer.

[0026] (4) Ag is added to CMT welding wire: From the Al-Ag binary phase diagram, it can be seen that Ag has a high solid solubility in Al. Therefore, adding Ag to the welding wire can not only improve the fluidity of the welding wire, but also improve the strength of the cladding layer. In addition, Ag has a higher melting point than Al, which can stabilize the arc.

[0027] (5) Si element is added to both laser cladding alloy powder and CMT welding wire: According to the Al-Si phase diagram, the solid solubility of Si in Al is second only to Zn and Ag. Therefore, adding Si to either the laser cladding layer or the CMT cladding layer can play a role in solid solution strengthening and improve the strength of the laser cladding layer and the CMT cladding layer. Si also has a large solubility in Fe, so adding Si to the laser cladding layer can improve the bonding performance between the laser cladding layer and the steel layer. In addition, Si is a deoxidizing element that can deoxidize the cladding layer, thereby avoiding oxidation of the remaining alloy elements.

[0028] (6) Sn element is added to the laser cladding alloy powder: From the Al-Sn binary phase diagram, it can be seen that the two will not generate a brittle phase. Sn has a low melting point of 231°C. Sn, Zn and Cu can form a low melting point alloy, thereby further reducing the melting point of the laser cladding layer and reducing the diffusion of Fe elements in the steel matrix, thereby fundamentally inhibiting the formation of Fe-Al brittle phase.

[0029] (7) Mg element is added to CMT welding wire: According to the Al-Mg binary phase diagram, the maximum solid solution content of Mg in Al is 17.1wt.%. Therefore, the added Mg is dissolved in the Al matrix, thereby strengthening the Al cladding layer and improving the strength of the aluminum-steel gradient joint.

[0030] The purity of each raw material powder in the laser cladding alloy powder is ≥99.9%.

[0031] The particle size of each raw material powder in the aluminum-based welding wire for CMT welding is 100~200 mesh.

[0032] The weld skin of aluminum-based welding wire for CMT welding is pure aluminum strip with a thickness of 0.4mm and a width of 7mm.

[0033] The powder filling rate of aluminum-based welding wire for CMT welding is controlled at 25wt%~30wt%.

[0034] The preparation method of alloy powder for laser cladding includes the following specific steps: Step 1: Weigh 20.0-30.0% Zn powder, 20.0-30.0% Cu powder, 5.0-10.0% Si powder, 5.0-10.0% Sn powder, and the balance Al, respectively, and the sum of the mass percentages of the above components is 100%; Step 2: Mix the raw material powders in step 1, melt them in vacuum, and prepare powder by gas atomization method; In step 2, vacuum melting equipment is used, N2 is used as atomizing gas, the atomizing pressure is 6MPa, and the superheat of the melt is maintained between 100 and 150°C during the atomization process; Step 3: Screening the atomized raw material powder for particle size; In step 3, the particle size range of the raw material powder after sieving is 25-53 μm, i.e. 270-500 mesh; The fluidity requirement of the raw material powder after screening is 25~40 s / 100g; Step 4: Vacuum pack the prepared powder for later use.

[0035] The preparation method of aluminum-based welding wire for CMT welding, the specific steps are as follows: Step 1: Weigh 20.0-30.0% Zn powder, 20.0-30.0% Ag powder, 10.0-20.0% Cu powder, 5.0-10.0% Si powder, 5.0-9.0% Mg powder, and the rest Al powder, respectively, by mass percentage, and the sum of the mass percentages of the above components is 100%; Step 2: The powder weighed in step 1 is placed in a vacuum heating furnace and heated at a temperature of 100-160°C for 1-2 hours to remove the crystal water in the powder; the dried powder is placed in a powder mixer for sufficient mixing for 1-2 hours; Step 3: Use alcohol to remove grease from the surface of the pure aluminum strip, and wrap the powder prepared in step 2 in the pure aluminum strip through a flux-cored wire drawing device. The aperture of the first drawing die is 2.6 mm; the powder filling rate is controlled at 25wt%~30wt%; Step 4: After the first drawing process is completed, the die aperture is reduced successively, and finally a flux-cored welding wire with a diameter of 1.2 mm is obtained; Step 5: After the flux-cored welding wire is drawn, it is wound on the welding wire reel by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for standby use.

[0036] The present invention also provides a laser + CMT composite preparation method for an aluminum-steel gradient structure, wherein the aluminum-steel gradient structure is prepared by using the prepared laser cladding powder and the aluminum-based welding wire for CMT welding, such as Figure 1 As shown, the specific steps are as follows: (1) First, the alloy powder for laser cladding according to claim 1 is used to prepare a laser cladding layer on a steel substrate (Q345), the laser power is 1 kW to 3 kW, and the thickness of the cladding layer is 1.0 mm to 1.5 mm; (2) Next, the aluminum-based welding wire for CMT welding according to claim 1 is used to perform cladding welding on the laser cladding layer. When the first layer is cladding welded, the welding current is 150A~180A, and the thickness of the cladding layer is 2mm~3mm; when the second layer is cladding welded, the welding current is 180A~200A, and the thickness of the cladding layer is 3mm~4mm; during CMT cladding welding, the interlayer temperature is controlled at 50℃~100℃; (3) Finally, ER1100 pure aluminum welding wire is used to perform arc cladding on the second CMT cladding layer to prepare an aluminum layer. The welding current is 150A~200A, the thickness of the cladding layer is 10mm~15mm, and the interlayer temperature is controlled at 50℃~100℃ during cladding.

[0037] Example 1 The preparation method of alloy powder for laser cladding includes the following specific steps: Step 1: Weigh 20.0% Zn powder, 20.0% Cu powder, 5.0% Si powder, 5.0% Sn powder, and the balance Al respectively by mass percentage, and the sum of the mass percentages of the above components is 100%; Step 2: Mix the raw material powders in step 1, melt them in vacuum, and prepare powder by gas atomization method; Step 3: Screen the atomized raw material powder for particle size. Step 4: Vacuum pack the prepared powder for later use.

[0038] In step 2, vacuum melting equipment is used, N2 is used as the atomizing gas, the atomizing pressure is 6MPa, and the superheat of the melt is maintained at 100°C during the atomization process.

[0039] In step 3, the particle size range of the raw material powder after sieving is 25 μm.

[0040] The fluidity requirement of the raw material powder after screening is 25 s / 100g.

[0041] The purity of each raw material powder in the laser cladding alloy powder is ≥99.9%; The preparation method of aluminum-based welding wire for CMT welding, the specific steps are as follows: Step 1: Weigh 20.0% Zn powder, 20.0% Ag powder, 10.0% Cu powder, 5.0% Si powder, 5.0% Mg powder, and the rest Al powder by mass percentage, and the sum of the mass percentages of the above components is 100%; The particle size of each raw material powder in the aluminum-based welding wire for CMT welding is 100 mesh.

[0042] Step 2: The powder weighed in step 1 is placed in a vacuum heating furnace and heated at 100°C for 1 hour to remove the crystal water in the powder; the dried powder is placed in a powder mixer for sufficient mixing for 1 hour; Step 3: Use alcohol to remove the grease on the surface of the pure aluminum strip, and wrap the powder prepared in step 2 in the pure aluminum strip through the flux-cored wire drawing equipment. The aperture of the first drawing die is 2.6mm; the pure aluminum strip has a thickness of 0.4mm and a width of 7mm; the powder filling rate of the aluminum-based welding wire for CMT welding is controlled at 25wt%; Step 4: After the first drawing process is completed, the die aperture is reduced successively, and finally a flux-cored welding wire with a diameter of 1.2 mm is obtained.

[0043] Step 5: After the flux-cored welding wire is drawn, it is wound on the welding wire reel by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for standby use.

[0044] The laser + CMT composite preparation method of aluminum-steel gradient structure has the following specific steps (such as Figure 1 shown): (1) First, the above alloy powder for laser cladding is used to prepare a laser cladding layer on a steel substrate, with a laser power of 1 kW and a cladding layer thickness of 1.0 mm; (2) Next, two layers of CMT cladding layers were clad on the laser cladding layer using the aluminum-based welding wire for CMT welding. The welding current for the first layer was 150 A and the thickness of the cladding layer was 2 mm. The welding current for the second layer was 180 A and the thickness of the cladding layer was 3 mm. The interlayer temperature during CMT cladding was controlled at 50 °C.

[0045] (3) Finally, ER1100 pure aluminum welding wire was used to perform arc cladding on the above CMT cladding layer to prepare an aluminum layer. The welding current was 150A, the thickness of the cladding layer was 10mm, and the interlayer temperature was controlled at 50°C during cladding.

[0046] After testing, the tensile strength of the aluminum-steel gradient structure is 251MPa.

[0047] Example 2 The preparation method of alloy powder for laser cladding includes the following specific steps: Step 1: Weigh 30.0% Zn powder, 30.0% Cu powder, 10.0% Si powder, 10.0% Sn powder, and the balance Al respectively by mass percentage, and the sum of the mass percentages of the above components is 100%; The purity of each raw material powder in the laser cladding alloy powder is ≥99.9%; Step 2: Mix the raw material powders in step 1, melt them in vacuum, and prepare powder by gas atomization method; Step 3: Screen the atomized raw material powder for particle size. Step 4: Vacuum pack the prepared powder for later use.

[0048] In step 2, vacuum melting equipment is used, N2 is used as the atomizing gas, the atomizing pressure is 6MPa, and the superheat of the melt is maintained between 150°C during the atomization process.

[0049] In step 3, the particle size range of the raw material powder after sieving is 50 μm.

[0050] The fluidity requirement of the raw material powder after screening is 30 s / 100g.

[0051] The preparation method of aluminum-based welding wire for CMT welding, the specific steps are as follows: Step 1: Weigh 30.0% Zn powder, 30.0% Ag powder, 20.0% Cu powder, 10.0% Si powder, 9.0% Mg powder, and the rest Al powder by mass percentage, and the sum of the mass percentages of the above components is 100%; The particle size of each raw material powder in the aluminum-based welding wire for CMT welding is 200 mesh; Step 2: The powder weighed in step 1 is placed in a vacuum heating furnace and heated at 160° C. for 2 hours to remove the crystal water in the powder; the dried powder is placed in a powder mixer for sufficient mixing for 2 hours; Step 3: Use alcohol to remove grease on the surface of the pure aluminum strip, and wrap the powder prepared in step 2 in the pure aluminum strip through the flux-cored wire drawing equipment. The aperture of the first drawing die is 2.6mm; the pure aluminum strip has a thickness of 0.4mm and a width of 7mm; the powder filling rate of the aluminum-based welding wire for CMT welding is controlled at 30wt%.

[0052] Step 4: After the first drawing process is completed, the die aperture is reduced successively, and finally a flux-cored welding wire with a diameter of 1.2 mm is obtained.

[0053] Step 5: After the flux-cored welding wire is drawn, it is wound on the welding wire reel by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for standby use.

[0054] The laser + CMT composite preparation method of aluminum-steel gradient structure has the following specific steps (such as Figure 1 shown): (1) First, the above alloy powder for laser cladding is used to prepare a laser cladding layer on a steel substrate, the laser power is 3 kW, and the cladding layer thickness is 1.5 mm; (2) Next, two layers of CMT cladding layers were clad on the laser cladding layer using the aluminum-based welding wire for CMT welding. The welding current for the first layer was 180 A and the thickness of the cladding layer was 3 mm. The welding current for the second layer was 200 A and the thickness of the cladding layer was 4 mm. The interlayer temperature during CMT cladding was controlled at 100 °C.

[0055] (3) Finally, ER1100 pure aluminum welding wire was used to perform arc cladding on the above CMT cladding layer to prepare an aluminum layer. The welding current was 200A, the thickness of the cladding layer was 15 mm, and the interlayer temperature was controlled at 100°C during cladding.

[0056] Figure 2The laser cladding layer microstructure in the aluminum-steel gradient structure prepared in Example 2. As can be seen from the figure, the laser cladding layer is mainly composed of Al solid solution, and no defects such as cracks and pores are observed.

[0057] Figure 3 The microstructure of the CMT cladding layer in the aluminum-steel gradient structure prepared in Example 2. As can be seen from the figure, the CMT cladding layer is mainly composed of Al solid solution, with obvious dendrite morphology, and no defects such as cracks and pores are observed.

[0058] Figure 4 This is the tensile fracture scanning electron microscope morphology of the aluminum-steel gradient structure prepared in Example 2. As can be seen from the figure, the fracture is mainly dimple morphology, indicating that the aluminum-steel gradient structure has good toughness and also proves that the gradient structure does not generate Fe-Al brittle phase.

[0059] After testing, the tensile strength of the aluminum-steel gradient structure is 267MPa.

[0060] Example 3 The preparation method of alloy powder for laser cladding includes the following specific steps: Step 1: Weigh 25.0% Zn powder, 25.0% Cu powder, 7.0% Si powder, 7.0% Sn powder, and the balance Al respectively by mass percentage, and the sum of the mass percentages of the above components is 100%; The purity of each raw material powder in the laser cladding alloy powder is ≥99.9%; Step 2: Mix the raw material powders in step 1, melt them in vacuum, and prepare powder by gas atomization method; Step 3: Screen the atomized raw material powder for particle size. Step 4: Vacuum pack the prepared powder for later use.

[0061] In step 2, vacuum melting equipment is used, N2 is used as the atomizing gas, the atomizing pressure is 6 MPa, and the superheat of the melt is maintained between 130°C during the atomization process.

[0062] In step 3, the particle size range of the raw material powder after sieving is 53 μm.

[0063] The fluidity requirement of the raw material powder after screening is 40 s / 100g.

[0064] The preparation method of aluminum-based welding wire for CMT welding, the specific steps are as follows: Step 1: Weigh 25.0% Zn powder, 25.0% Ag powder, 15.0% Cu powder, 7.0% Si powder, 7.0% Mg powder, and the rest Al powder by mass percentage, and the sum of the mass percentages of the above components is 100%; The particle size of each raw material powder in the aluminum-based welding wire for CMT welding is 200 mesh; Step 2: The powder weighed in step 1 is placed in a vacuum heating furnace and heated at 130° C. for 1.5 hours to remove the crystal water in the powder; the dried powder is placed in a powder mixer for sufficient mixing for 1.5 hours; Step 3: Use alcohol to remove the grease on the surface of the pure aluminum strip, and wrap the powder prepared in step 2 in the pure aluminum strip through the flux-cored wire drawing equipment. The aperture of the first drawing die is 2.6mm; the thickness of the pure aluminum strip is 0.4mm and the width is 7mm; the powder filling rate of the aluminum-based welding wire for CMT welding is controlled at 28wt%; Step 4: After the first drawing process is completed, the die aperture is reduced successively, and finally a flux-cored welding wire with a diameter of 1.2 mm is obtained.

[0065] Step 5: After the flux-cored welding wire is drawn, it is wound on the welding wire reel by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for standby use.

[0066] The laser + CMT composite preparation method of aluminum-steel gradient structure has the following specific steps (such as Figure 1 shown): (1) First, the above alloy powder for laser cladding is used to prepare a laser cladding layer on a steel substrate, the laser power is 2 kW, and the cladding layer thickness is 1.3 mm; (2) Next, two layers of CMT cladding layers were clad on the laser cladding layer using the aluminum-based welding wire for CMT welding. The welding current for the first layer was 170 A and the thickness of the cladding layer was 2.5 mm. The welding current for the second layer was 190 A and the thickness of the cladding layer was 3.5 mm. The interlayer temperature during CMT cladding was controlled at 70°C.

[0067] (3) Finally, ER1100 pure aluminum welding wire was used to perform arc cladding on the above CMT cladding layer to prepare an aluminum layer. The welding current was 170A, the thickness of the cladding layer was 13 mm, and the interlayer temperature was controlled at 70°C during cladding.

[0068] After testing, the tensile strength of the aluminum-steel gradient structure is 228MPa.

[0069] Example 4 The preparation method of alloy powder for laser cladding includes the following specific steps: Step 1: Weigh 22.0% Zn powder, 22.0% Cu powder, 6.0% Si powder, 6.0% Sn powder, and the balance Al, respectively, and the sum of the mass percentages of the above components is 100%; The purity of each raw material powder in the laser cladding alloy powder is ≥99.9%; Step 2: Mix the raw material powders in step 1, melt them in vacuum, and prepare powder by gas atomization method; Step 3: Screen the atomized raw material powder for particle size. Step 4: Vacuum pack the prepared powder for later use.

[0070] In step 2, vacuum melting equipment is used, N2 is used as the atomizing gas, the atomizing pressure is 6MPa, and the superheat of the melt is maintained between 120°C during the atomization process.

[0071] In step 3, the particle size range of the raw material powder after sieving is 45 μm.

[0072] The fluidity requirement of the raw material powder after screening is 35 s / 100g.

[0073] The preparation method of aluminum-based welding wire for CMT welding, the specific steps are as follows: Step 1: Weigh 22.0% Zn powder, 22.0% Ag powder, 12.0% Cu powder, 6.0% Si powder, 6.0% Mg powder, and the rest Al powder by mass percentage, and the sum of the mass percentages of the above components is 100%; The particle size of each raw material powder in the aluminum-based welding wire for CMT welding is 100 mesh; Step 2: The powder weighed in step 1 is placed in a vacuum heating furnace and heated at 120°C for 1.2 hours to remove the crystal water in the powder; the dried powder is placed in a powder mixer for sufficient mixing for 1.2 hours; Step 3: Use alcohol to remove grease on the surface of the pure aluminum strip, and wrap the powder prepared in step 2 in the pure aluminum strip through the flux-cored wire drawing equipment. The aperture of the first drawing die is 2.6mm; the pure aluminum strip has a thickness of 0.4mm and a width of 7mm; the powder filling rate of the aluminum-based welding wire for CMT welding is controlled at 25wt%.

[0074] Step 4: After the first drawing process is completed, the die aperture is reduced successively, and finally a flux-cored welding wire with a diameter of 1.2 mm is obtained.

[0075] Step 5: After the flux-cored welding wire is drawn, it is wound on the welding wire reel by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for standby use.

[0076] The laser + CMT composite preparation method of aluminum-steel gradient structure has the following specific steps (such as Figure 1 shown): (1) First, the above alloy powder for laser cladding is used to prepare a laser cladding layer on a steel substrate, the laser power is 1.5 kW, and the thickness of the cladding layer is 1.2 mm; (2) Next, two layers of CMT cladding layers were clad on the laser cladding layer using the aluminum-based welding wire for CMT welding. The welding current for the first layer was 165 A and the thickness of the cladding layer was 2.2 mm. The welding current for the second layer was 185 A and the thickness of the cladding layer was 3.2 mm. The interlayer temperature during CMT cladding was controlled at 60°C.

[0077] (3) Finally, ER1100 pure aluminum welding wire was used to perform arc cladding on the above CMT cladding layer to prepare an aluminum layer. The welding current was 165A, the thickness of the cladding layer was 10-15mm, and the interlayer temperature was controlled at 60°C during cladding.

[0078] After testing, the tensile strength of the aluminum-steel gradient structure is 255MPa.

[0079] Example 5 The preparation method of alloy powder for laser cladding includes the following specific steps: Step 1: Weigh 29.0% Zn powder, 29.0% Cu powder, 9.0% Si powder, 9.0% Sn powder, and the balance Al, respectively, by mass percentage, and the sum of the mass percentages of the above components is 100%; The purity of each raw material powder in the laser cladding alloy powder is ≥99.9%; Step 2: Mix the raw material powders in step 1, melt them in vacuum, and prepare powder by gas atomization method; Step 3: Screen the atomized raw material powder for particle size. Step 4: Vacuum pack the prepared powder for later use.

[0080] In step 2, vacuum melting equipment is used, N2 is used as the atomizing gas, the atomizing pressure is 6MPa, and the superheat of the melt is maintained between 140°C during the atomization process.

[0081] In step 3, the particle size range of the raw material powder after sieving is 53 μm.

[0082] The fluidity requirement of the raw material powder after screening is 40 s / 100g.

[0083] The preparation method of aluminum-based welding wire for CMT welding, the specific steps are as follows: Step 1: Weigh 29.0% Zn powder, 29.0% Ag powder, 19.0% Cu powder, 9.0% Si powder, 8.5.0% Mg powder, and the rest Al powder by mass percentage, and the sum of the mass percentages of the above components is 100%; The particle size of each raw material powder in the aluminum-based welding wire for CMT welding is 100 mesh; Step 2: The powder weighed in step 1 is placed in a vacuum heating furnace and heated at 110°C for 1.9 hours to remove the crystal water in the powder; the dried powder is placed in a powder mixer for sufficient mixing for 1.8 hours; Step 3: Use alcohol to remove grease on the surface of the pure aluminum strip, and wrap the powder prepared in step 2 in the pure aluminum strip through the flux-cored wire drawing equipment. The aperture of the first drawing die is 2.6mm; the thickness of the pure aluminum strip is 0.4mm and the width is 7mm; the powder filling rate of the aluminum-based welding wire for CMT welding is controlled at 25wt%.

[0084] Step 4: After the first drawing process is completed, the die aperture is reduced successively, and finally a flux-cored welding wire with a diameter of 1.2 mm is obtained.

[0085] Step 5: After the flux-cored welding wire is drawn, it is wound on the welding wire reel by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for standby use.

[0086] The laser + CMT composite preparation method of aluminum-steel gradient structure has the following specific steps (such as Figure 1 shown): (1) First, the above alloy powder for laser cladding is used to prepare a laser cladding layer on a steel substrate, the laser power is 2.5 kW, and the thickness of the cladding layer is 1.45 mm; (2) Next, two layers of CMT cladding layers were clad on the laser cladding layer using the aluminum-based welding wire for CMT welding. The welding current for the first layer was 175 A and the thickness of the cladding layer was 2.1 mm. The welding current for the second layer was 195 A and the thickness of the cladding layer was 3.8 mm. The interlayer temperature during CMT cladding was controlled at 55°C.

[0087] (3) Finally, ER1100 pure aluminum welding wire was used to perform arc cladding on the above CMT cladding layer to prepare an aluminum layer. The welding current was 195A, the thickness of the cladding layer was 14.5mm, and the interlayer temperature was controlled at 74°C during cladding.

[0088] After testing, the tensile strength of the aluminum-steel gradient structure is 268MPa.

[0089] Example 6 The preparation method of alloy powder for laser cladding includes the following specific steps: Step 1: Weigh 29.0% Zn powder, 28.0% Cu powder, 8.0% Si powder, 9.0% Sn powder, and the balance Al, respectively, by mass percentage, and the sum of the mass percentages of the above components is 100%; Step 2: Mix the raw material powders in step 1, melt them in vacuum, and prepare powder by gas atomization method; Step 3: Screen the atomized raw material powder for particle size. Step 4: Vacuum pack the prepared powder for later use.

[0090] In step 2, vacuum melting equipment is used, N2 is used as the atomizing gas, the atomizing pressure is 6MPa, and the superheat of the melt is maintained between 140°C during the atomization process.

[0091] In step 3, the particle size range of the raw material powder after sieving is 53 μm.

[0092] The fluidity requirement of the raw material powder after screening is 40 s / 100g.

[0093] The preparation method of aluminum-based welding wire for CMT welding, the specific steps are as follows: Step 1: Weigh 29.0% Zn powder, 29.0% Ag powder, 19.0% Cu powder, 9.0% Si powder, 7.5.0% Mg powder, and the rest Al powder by mass percentage, and the sum of the mass percentages of the above components is 100%; The particle size of each raw material powder in the aluminum-based welding wire for CMT welding is 100 mesh; Step 2: The powder weighed in step 1 is placed in a vacuum heating furnace and heated at 110°C for 1.9 hours to remove the crystal water in the powder; the dried powder is placed in a powder mixer for sufficient mixing for 1.8 hours; Step 3: Use alcohol to remove grease on the surface of the pure aluminum strip, and wrap the powder prepared in step 2 in the pure aluminum strip through the flux-cored wire drawing equipment. The aperture of the first drawing die is 2.6mm; the thickness of the pure aluminum strip is 0.4mm and the width is 7mm; the powder filling rate of the aluminum-based welding wire for CMT welding is controlled at 25wt%.

[0094] Step 4: After the first drawing process is completed, the die aperture is reduced successively, and finally a flux-cored welding wire with a diameter of 1.2 mm is obtained.

[0095] Step 5: After the flux-cored welding wire is drawn, it is wound on the welding wire reel by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for standby use.

[0096] The laser + CMT composite preparation method of aluminum-steel gradient structure has the following specific steps (such as Figure 1 shown): (1) First, the above alloy powder for laser cladding is used to prepare a laser cladding layer on a steel substrate, the laser power is 2.5 kW, and the thickness of the cladding layer is 1.45 mm; (2) Next, two layers of CMT cladding layers were clad on the laser cladding layer using the aluminum-based welding wire for CMT welding. The welding current for the first layer was 175 A and the thickness of the cladding layer was 2.1 mm. The welding current for the second layer was 195 A and the thickness of the cladding layer was 3.8 mm. The interlayer temperature during CMT cladding was controlled at 55°C.

[0097] (3) Finally, ER1100 pure aluminum welding wire was used to perform arc cladding on the above CMT cladding layer to prepare an aluminum layer. The welding current was 195A, the thickness of the cladding layer was 14.5mm, and the interlayer temperature was controlled at 74°C during cladding.

[0098] After testing, the tensile strength of the aluminum-steel gradient structure is 262MPa.

Claims

1. A welding material for preparing an aluminum-steel gradient structure, characterized in that: Including alloy powder for laser cladding and aluminum-based welding wire for CMT welding; The alloy powder for laser cladding includes the following components by mass percentage: Zn powder 20.0-30.0%, Cu powder 20.0-30.0%, Si powder 5.0-10.0%, Sn powder 5.0-10.0%, and the balance is Al; The aluminum-based welding wire for CMT welding comprises flux powder and welding skin, wherein the flux powder comprises the following components by mass percentage: Zn powder 20.0-30.0%, Ag powder 20.0-30.0%, Cu powder 10.0-20.0%, Si powder 5.0-10.0%, Mg powder 5.0-9.0%, and the rest is Al powder.

2. The welding material for preparing an aluminum-steel gradient structure according to claim 1, characterized in that: The purity of each raw material powder in the laser cladding alloy powder is ≥99.9%.

3. The welding material for preparing an aluminum-steel gradient structure according to claim 1, characterized in that: The particle size of each raw material powder in the aluminum-based welding wire for CMT welding is 100~200 mesh.

4. The welding material for preparing an aluminum-steel gradient structure according to claim 1, characterized in that: The weld skin of aluminum-based welding wire for CMT welding is pure aluminum strip with a thickness of 0.4mm and a width of 7mm.

5. The welding material for preparing an aluminum-steel gradient structure according to claim 1, characterized in that: The powder filling rate of aluminum-based welding wire for CMT welding is controlled at 25wt%~30wt%.

6. The welding material for preparing an aluminum-steel gradient structure according to claim 1, characterized in that: The preparation method of alloy powder for laser cladding includes the following specific steps: Step 1: Weigh 20.0-30.0% Zn powder, 20.0-30.0% Cu powder, 5.0-10.0% Si powder, 5.0-10.0% Sn powder, and the balance Al, respectively, and the sum of the mass percentages of the above components is 100%; Step 2: Mix the raw material powders in step 1, melt them in vacuum, and prepare powder by gas atomization method; In step 2, vacuum melting equipment is used, N2 is used as atomizing gas, the atomizing pressure is 6MPa, and the superheat of the melt is maintained between 100 and 150°C during the atomization process; Step 3: Screening the atomized raw material powder for particle size; In step 3, the particle size range of the raw material powder after screening is 25~53μm; The fluidity requirement of the raw material powder after screening is 25~40 s / 100g; Step 4: Vacuum pack the prepared powder for later use.

7. The welding material for preparing an aluminum-steel gradient structure according to claim 1, characterized in that: The preparation method of aluminum-based welding wire for CMT welding, the specific steps are as follows: Step 1: Weigh 20.0-30.0% Zn powder, 20.0-30.0% Ag powder, 10.0-20.0% Cu powder, 5.0-10.0% Si powder, 5.0-9.0% Mg powder, and the rest Al powder, respectively, by mass percentage, and the sum of the mass percentages of the above components is 100%; Step 2: The powder weighed in step 1 is placed in a vacuum heating furnace and heated at a temperature of 100-160°C for 1-2 hours to remove the crystal water in the powder; the dried powder is placed in a powder mixer for sufficient mixing for 1-2 hours; Step 3: Use alcohol to remove grease from the surface of the pure aluminum strip, and wrap the powder prepared in step 2 in the pure aluminum strip through a flux-cored wire drawing device. The aperture of the first drawing die is 2.6 mm; the powder filling rate is controlled at 25wt%~30wt%; Step 4: After the first drawing process is completed, the die aperture is reduced successively, and finally a flux-cored welding wire with a diameter of 1.2 mm is obtained; Step 5: After the flux-cored welding wire is drawn, it is wound on the welding wire reel by a wire winding machine and finally sealed in a flux-cored welding wire vacuum packaging bag for standby use.

8. A laser + CMT composite preparation method for an aluminum-steel gradient structure, characterized in that the specific steps are as follows: (1) First, the alloy powder for laser cladding according to claim 1 is used to prepare a laser cladding layer on a steel substrate, the laser power is 1 kW to 3 kW, and the thickness of the cladding layer is 1.0 mm to 1.5 mm; (2) Next, the aluminum-based welding wire for CMT welding according to claim 1 is used to perform overlay welding of two layers of CMT overlay layers on the above-mentioned laser cladding layer. When the first layer is overlaid, the welding current is 150A~180A, and the thickness of the overlay layer is 2mm~3mm; when the second layer is overlaid, the welding current is 180A~200A, and the thickness of the overlay layer is 3mm~4mm; during CMT overlay welding, the interlayer temperature is controlled at 50℃~100℃; (3) Finally, ER1100 pure aluminum welding wire is used to perform arc cladding on the second CMT cladding layer to prepare an aluminum layer. The welding current is 150A~200A, the thickness of the cladding layer is 10mm~15mm, and the interlayer temperature is controlled at 50℃~100℃ during cladding.

Citation Information

Patent Citations

  • Welding process for high damping copper alloy and steel

    CN101244480A

  • Self soldering flux-cored wire for aluminum / steel melt-soldering

    CN104972242A

  • Material for fusion welding of large-thickness aluminum-steel composite plate and preparation and welding method

    CN114393310A

  • Transition layer welding wire for preparing aluminum-steel composite structure and preparation and electric arc surfacing method

    CN114406518A

  • Steel-aluminum dissimilar metal laser-electric arc hybrid welding method for preparing pure nickel transition layer based on laser cladding

    CN117600657A

Cited By

  • Gradient cladding layer for superheater / reheater tube as well as preparation method and application of gradient cladding layer

    CN120291083A